‘You Know, This Conference Has No Legitimacy’: Eurosceptic Contestation of the Conference on the Future of Europe, Journal of Common Market Studies - Kotýnek Krotký, Jan
Amid the escalating contestation of European integration, the European Union (EU) endeavours to discover innovative approaches for bridging the gap between EU institutions and citizens while addressing the challenges posed by Eurosceptic actors. This article posits that Eurosceptic contestation may foster empowering dissensus. It expands its application beyond policy contestation to polity contestation. The article examines the Eurosceptic discourse surrounding the Conference on the Future of Europe (CoFoE), a pioneering deliberative attempt to bring citizens closer to EU institutions. Employing thematic analysis of various documents produced by the political groups of European Conservatives and Reformists (ECR), Identity and Democracy (ID), the Left, and Non-attached (NI), the article reveals two predominant themes through which these groups challenged the legitimacy of the CoFoE: manipulative governance and lack of representativity. The Eurosceptic critique closely echoes academic assessments of the CoFoE, casting doubt on claims that Eurosceptic narratives are without merit.
Keywords: national parliaments; European Parliament; European Union; democracy; preferences; interparliamentary cooperation